A TRANSITIVITY ANALYSIS OF TERTIARY INDONESIAN EFL STUDENTS’ ANALYTICAL EXPOSITIONS: A CASE STUDY - Amalia, Wafa; Emilia, Emi (LLT Journal: A Journal on Language and Language Teaching, 2025)
This paper presents the results of a study aiming to analyze analytical expositions written by tertiary Indonesian EFL students using transitivity system of systemic functional linguistics (SFL). The texts were created by nine students of English Language Education Study Program cohort 2024 at a state university in West Java, Indonesia, for the course of Reading and Writing for Academic Purposes. This study employed a qualitative case study with data obtained from the text analysis and a questionnaire distributed at the end of the course. The results of the analysis demonstrate that the students employed all six processes throughout the texts, namely material, relational, verbal, and mental processes, which were relevant to the linguistic features of an analytical exposition. Noteworthy cases in this study are students’ choices of process type for thesis statement and its placement, manners of utilizing verbal process as arguments, and alignments of process types between thesis and its restatement. The data from the questionnaire also supported the text analysis. In light to the findings, a recommendation is proposed for more exploration involving more participants, longer time, academic text types, and all systems of grammar in SFL.